Emotional Wellbeing and Cognitive Appraisals Among Law Enforcement Exposed to Child Sexually Explicit Materials - O’Brien, Jennifer E. (Criminal justice and behavior, 2024)
The cognitive appraisals of police investigators and forensic examiners working with child sexually explicit material (CSEM) may impact the level of distress they experience and its impact on holistic wellbeing. In the current study, we use an exploratory sequential mixed method design integrating quantitative and qualitative methodologies. Survey data were collected from 500 police investigators, forensic examiners, and others connected with the criminal justice system from across the United States; 258 of them also provided in-depth qualitative data. A principal components analysis uncovered initial components and latent probabilities, which were subsequently enriched with qualitative data coded using a grounded-theory approach. Results indicate that cognitive appraisals of law enforcement who investigate CSEM can be seen on two main axes: emotional vs cognitive and victim vs system. Cognitive-based and system-focused appraisals were associated with better wellbeing. Implications for officer wellness and future research are discussed.